An architecture for next-generation radio access networks. - Ghosh, S. (IEEE Network : the magazine of global information exchange)
With fourth-generation wireless technologies envisioned to provide high bandwidth for content-rich multimedia applications, next-generation mobile communication systems are well poised to lead the technology march. Incumbent with the new technology is the challenge of providing flexible, reconfigurable architectures capable of catering to the dynamics of the network, while providing cost-effective solutions for service providers. In this article we focus on IP-based radio access network architectures for next-generation mobile systems. We provide an insight into wireless mesh-based connectivity for the RAN network elements - using short high-bandwidth links to interconnect the network entities in a multihop mesh network for backhauling traffic to the core. A generic self-similar fractal topology, using optical wireless transmission technology, is described. We study the performance of the architecture and conclude that mesh-based architectures are well suited to provide highly scalable, dynamic radio access networks with carrier-class features at significantly low system costs.